An approach to the study of obesity and depression in a sample of Mexican adolescents in northern Mexico - Meza Peña, Cecilia; Pompa Guajardo, Edith Gerardina (2018)
The study investigates the prevalence of obesity and depression, and the strength of association between variables in a sample of adolescents in the North of Mexico. A sample of 849 adolescents was evaluated with the Depression Scale for Children. The results showed a high prevalence of depressive symptoms in adolescents who are overweight and obese (57.9%). The Obesity is not related statistically with the Depression rate and no association between variables was found when calculated by gender. The study could not confirm a relationship between obesity and depression, but the high prevalence of depressive symptoms in the studied population is of special interest, no matter the weight group they belong.